PENGARUH LATIHAN PUSH-UP DAN LATIHAN WHOLE PART WHOLE TERHADAP KETEPATAN PUKULAN OI ZUKI CHUDAN PADA SISWA EKSTRAKURIKULER KARATE SMPN 1 RANTAU PANJANG - M.Arjun Apriliansyah; Yasir Arafat; Jujur Gunawan Manullang (STKIP Subang, 2023)
Test and post-test experiments with 16 meetings. The research instrument was in the form of the oi zuki chudan punch test for 2 trials and the highest results would be used as pre-test and post-test scores. The object in this study was taken by total sampling, namely karate extracurricular students at SMPN 1 Rantau Panjang. The research location was determined based on sample data collection, namely at SMPN 1 Rantau Panjang with a total of 20 students. The data analysis technique used is hypothesis testing with t-test analysis. The results of the study obtained a tcount of 15.47 > ttable of 5.131 indicating that